2016
DOI: 10.1002/2015ja022194
|View full text |Cite
|
Sign up to set email alerts
|

Global equatorial plasma bubble occurrence during the 2015 St. Patrick's Day storm

Abstract: An analysis of the occurrence of equatorial plasma bubbles (EPBs) around the world during the 2015 St. Patrick's Day geomagnetic storm is presented. A network of 12 Global Positioning System receivers spanning from South America to Southeast Asia was used, in addition to colocated VHF receivers at three stations and four nearby ionosondes. The suppression of postsunset EPBs was observed across most longitudes over 2 days. The EPB observations were compared to calculations of the linear Rayleigh‐Taylor growth r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
101
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 84 publications
(117 citation statements)
references
References 51 publications
15
101
1
Order By: Relevance
“…Our observations are also reinforced by what was found by Carter et al [2016], who reported the weakening of the interplanetary electric field at ∼00 UT on 18 March (corresponding to the postmidnight sector in SEA), which led to the weakening of the RTI growth rate. In the following days, Carter et al [2016] reported also the absence of RTI formation.…”
Section: Magnetic Data 221 Ground-based Magnetometerssupporting
confidence: 90%
See 1 more Smart Citation
“…Our observations are also reinforced by what was found by Carter et al [2016], who reported the weakening of the interplanetary electric field at ∼00 UT on 18 March (corresponding to the postmidnight sector in SEA), which led to the weakening of the RTI growth rate. In the following days, Carter et al [2016] reported also the absence of RTI formation.…”
Section: Magnetic Data 221 Ground-based Magnetometerssupporting
confidence: 90%
“…h 0 F as measured at Sanya from 20 to 24 March 2015. are in agreement with the modeled RTI growth rate and amplitude scintillation observations in Bangkok (13.75°N, 100.48°E) reported inFigure 2lofCarter et al [2016]. are in agreement with the modeled RTI growth rate and amplitude scintillation observations in Bangkok (13.75°N, 100.48°E) reported inFigure 2lofCarter et al [2016].…”
supporting
confidence: 90%
“…These results are consistent with those reported by Carter et al . [] using a global network of 12 GPS receiving stations. Carter et al .…”
Section: Discussionmentioning
confidence: 99%
“…C/NOFS observations during the 2008-2009 solar minimum that were reported by Dao et al (2011) showed convincing evidence that lower atmospheric forcing might play a significant role in EPB generation. In addition to these observations, modeling has shown that R-T growth is still possible under small/negative upward plasma drift conditions (Carter et al 2016) and that EPB development and characteristics can be significantly influenced by the presence of atmospheric gravity waves (Retterer and Roddy 2014).…”
Section: Introductionmentioning
confidence: 99%